2020
DOI: 10.37394/232015.2020.16.69
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Structural Properties of Fire Clay Bricks After Adding Cigarette Filters

Abstract: Cigarette filters are one of the most littered objects in the world that damage the environment. Incorporation in construction bricks offers the prospect of limiting damage and solves the recyclability problem for a typical non-biodegradable waste. This paper aims to explore that prospect, by adding cigarette filters in the production of two samples of fired clay bricks with the cigarette filters comprising 5% and 10% of the volume. The mixing and molding processes were done manually which had an effect on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The results presented in this research is consistent with the results presented by Abdullatif et al (2020). In both studies, the compression strength of fire clay brick dropped after adding fibre waste to the specimens.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results presented in this research is consistent with the results presented by Abdullatif et al (2020). In both studies, the compression strength of fire clay brick dropped after adding fibre waste to the specimens.…”
Section: Discussionsupporting
confidence: 92%
“…In many countries, organic wastes are disposed of by dumping them in landfills, leading to more pollution and negative impacts on the environment [4,5,6]. Therefore, local researchers focus on recognising the best technology to dispose of organic wastes by recycling and utilising them as raw materials in the production chains of other industries [7][8].…”
Section: Introductionmentioning
confidence: 99%
“…18 Various washing and chemical treatments were also carried out depending on the desired products. But different researchers tried to develop various applications of CBFs in different recycled materials for nonwoven production, 19 sound absorbing material, 20 nanocrystal cellulose, 21 supporting material for bricks and steel manufacturing, 22 Asphalt concrete, 23 storage for energy in supercapacitor electrode, 24 and acetate fiber extraction from cigarette butts and characterization of their properties. 25 It has been observed that recently researchers tried to recycle and reuse the CBFs in different applications, and a considerable recycling rate of recent years was found for the production of carbon-based materials of around 27.27%, for building/construction materials, hydrophobic fibers 9.09%, supercapacitors 6.06%, paper 3.03%, corrosion control 6.06%, insect control 9.09%, sound absorber 6.06%, and biofilm carrier 6.06%.…”
Section: Introductionmentioning
confidence: 99%
“…The growing population exposed a huge pressure on the city's urban infrastructure especially the transport infrastructure. Transportations considered the main resource of greenhouse gas emissions: the carbon emissions emitted from transportations sector are about 30% of the total emission produced in developed countries and about 23% of the total carbon emissions emitted globally (Moussa, 2021).…”
Section: Introductionmentioning
confidence: 99%